AQAID AL-KHAMSINA MENURUT AHLUSSUNNAH WAL JAMA’AH - Adenan Adenan; Ismet Sari; Sutan M. Arfierdin Pohan (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
The rise of evil that existed in this period began from free association, abuse of drugs, theft and others. The moral deterioration is very much happening and the way to cope with it is by deepening the science of religion, which is with a lot of scientific knowledge of Tauhid. The science of Tauhid is a science that discusses the attributes of Allah SWT and his Messenger or called Aqaid Al-Khamsina. By studying the science of Tauhid can certainly reduce the number of criminality because by learning the science of Tauhid means a person's behavior will be much better. This research aims to determine the meaning of Aqaid Al-Khamsina and the explanation of each of these qualities. This research is included in Library research.  Primary data sources include the book by Imam Muhammad bin as-Sanusi named Umm al-Barahin, the publisher city of Kediri, the publisher name Santri Salaf Press, in the year 2015 and the book of Sheikh Muhammad Al-Fudholi named Kifayatul Awam, the publisher of Surabaya, the name of publisher Mutiara Ilmu, in the year 2018.  The secondary sources are books related to Aqaid Al-Khamsina, which is a book by Siradjuddin Abbas named I'itiqad Ahlussunnah Wal Jama'ah, a book by Abu Fikri Ihsani called Encyclopedia of Allah, a book by Imam Abil Izz Al-Hanafi named Tahdzib Syarah Aqidah Thahawiyah. In analyzing this research researchers use the Content analysis method (content analysis) is by means of drawing conclusions from several references that have been chosen, compared and combined.  The results of the research obtained is that Aqaid Al-Khamsina is a nature of Allah SWT and its Apostles that if in total there is 50 consisting of 20 mandatory nature of God, 20 impossibly god nature, 1 Jaiz nature, 4 mandatory nature of the Apostle, 4 the odds of the Apostle and 1 character Jaiz apostle. All of our mandatory qualities are known and Imani as the perfection of the creed.Keywords: Ahlussunnah Wal Jama'ah, Aqaid Al-Khamsina, Akidah, Tauhid.